RETRACTED: Sanhua Decoction, a Classic Herbal Prescription, Exerts Neuroprotection Through Regulating Phosphorylated Tau Level and Promoting Adult Endogenous Neurogenesis After Cerebral Ischemia/Reperfusion Injury - Fu, Deng-Lei; Li, Ji-Huang; Shi, Yi-Hua; Zhang, Xi-Le; Lin, Yan; Zheng, Guo-Qing (Frontiers in Physiology, 2020)
Abstract Background: Ischemia stroke is the leading cause of death and long-term disability. Sanhua Decoction (SHD), a classic Chinese herbal prescription, has been used for ischemic stroke for about thousands of years. Here, we aim to investigate the neuroprotective effects of SHD on cerebral ischemia/reperfusion (CIR) injury rat models. Methods: The male Sprague-Dawley rats (body weight, 250-280 g; age, 7-8 w) were randomly divided into sham group, CIR group and SHD group, and were further divided into subgroups according to different time points at 6h, 1d, 3d, 7d, 14d, 21d and 28d respectively. The SHD group received intragastric administration of SHD at 10 g · kg-1 · d-1. The focal CIR models were induced by middle cerebral artery occlusion according to Longa’s method, while sham group had the same operation without suture insertion. Neurological deficit score (NDS) was evaluated using the Longa’s scale. BrdU, doublecortin (DCX) and glial fibrillary acidic protein (GFAP) were used to label proliferation, migration and differentiation of nerve cells before being observed by immunofluorescence. The expression of reelin, total tau (t-tau) and phosphorylated tau (p-tau) were evaluated by western blot and RT-qPCR. Results: SHD can significantly improve NDS at 1d, 3d, 7d and 14d (P<0.05), increase the number of BrdU positive and BrdU/DCX positive cells in subventricular zone at 3d, 7d and 14d (P<0.05), upregulate BrdU/GFAP positive cells in the ischemic penumbra at 28d after CIR (P<0.05), and reduce p-tau level at 1d, 3d, 7d and 14d (P<0.05). There was no significant difference on reelin and t-tau level between 3 groups at each time points after CIR. Conclusions: SHD exerts neuroprotection probably by regulating p-tau level and promoting the proliferation, migration and differentiation of endogenous neural stem cells, accompanying with neurobehavioral recovery.